Kekuataan Hukum Perjanjian Lisan Antara Agen Kelapa Sawit Dengan Petani - Sihite, Sri Rumada; Sinaga, Roulinta Yesvery (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2024)
Introduction: Oral agreements that occur between oil palm farmers and oil palm agents where the agreement is buying and selling oil palm orally. However, there is a problem where the palm oil agent turns out to be in default. This writing is to examine the oral agreement between oil palm agents and oil palm farmers in Teluk Dalam Village. Purposes of the Research: The purpose of this research is to know the legal force of oral agreements between oil palm agents and oil palm farmers in the village of Teluk Pulai. Methods of the Research: The research method is normative juridical with the type of library research and field data. Results Originality of the Research: The results of the oral agreement on the sale of oil palm between the oil palm agent and the oil palm grower which of course this is considered valid due to the fulfillment of the elements and conditions that have been determined. The agreement made must be serious, in good faith and know the provisions of the object, price and capacity between the parties, it is necessary for the parties to comply with these provisions to ensure the validity and enforceability of the sale and purchase agreement in the context of civil law in Indonesia.